Advances in Food Processing Technology - Jia, Jingdun; Liu, Donghong; Ma, Haile; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book introduces readers to essential advances in the application of physical processing technology in food processing that have been made in recent years. It analyzes and describes the application of Power Ultrasound, Pulsed Electric Field, Supercritical-CO2, and Infrared Heating in the contexts of food sterilization, extraction, modification, drying and safety control. Covering all aspects of food physical processing, from basic principles to the latest technological developments, it offers a valuable application guide for food engineers and food researchers alike. .
Innovation of Food Physical Processing Technology in China -- The Basic Concept of Food Physical Processing -- Green Separation Technologies in Food Processing: Supercritical-CO2 -- Research Progress on Power Ultrasound Technology -- Power Ultrasound for Extraction and Modification of Polysaccharides from Medicinal Fungi -- Pulsed Electric Fields Assisted Extraction of Bioactive Compounds -- Pulsed Electric Fields Processing of Protein-Based Foods -- Supercritical-CO2 (SC-CO2) as Non-Thermal Alternative Technology for Food Safety -- Physical and Mechanic Pretreatment of Raw Material for Health-Promoting Component Extraction -- Infrared Heating for Improved Drying Efficiency, Food Safety and Quality of Rice.
Keywords: Food science; Nutrition .; Agriculture; Manufactures; Chemistry, Technical; Food Science; Nutrition; Agriculture; Machines, Tools, Processes; Industrial Chemistry